The Story of Arabic Language: Historical Linguistics Study - AL-dihaymawee, Doaa Taher Matrood; Merzah, Anwar Abbas; Abdul Ridha, Hussein Mohammed (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
In this study, the researcher studies Arabic as one of the surviving languages of the Semitic family. This study also highlights the historical development of Arabic pre-Islam, after the advent of Prophet Mohammed and Islam, and after the end of the Islamic empire, and all the ups and downs that the Arabic Language went through during its development. Accordingly, these changes resulted in various Arabic languages, such as Classic Arabic, Modern Standard Arabic, and Colloquial Arabic. Most Arabs can speak standard Arabic in formal situations and a dialect for everyday communications; this case is named diglossia.